How proteins work. - Williamson, Michael P., 1957- (New York : Garland, 2012)
How Proteins Workis a clear, up-to-date and authoritative account of the principles that govern the way proteins work. This book will provide advanced undergraduate students in biochemistry and biophysics in vivo context for the standard protein sequence-structure-function model. The text will also serve as a valuable resource for graduate students and researchers looking for a reference on the fundamentals underlying protein function.